Liver needle biopsy in Iraninan pediatric patients: Diagnostic significance and pattern of liver diseases - Monajemzadeh Maryam; Tabriz Hedieh; Mahjoub Fatemeh; Fallahi Gholamhossein; Farahmand Fatemeh (Wolters Kluwer Medknow Publications, 2009)
We aimed at determining the pattern of liver disease in the Iranian children referred to the Medical Center of Children affiliated with the Tehran University of Medical Sciences. Materials and Methods: In a cross-sectional study conducted over 2 years, 425 liver needle biopsies were sent to the pathology laboratory of our center. Slides were prepared from paraffin-embedded blocks, stained by routine H & E and special stains and were then reviewed. The frequency of each disorder, separately and in combination with the age group or gender of the patients was calculated and compared with other similar studies. Results: The male to female ratio was 1.42:1. The age range was between 1 month and 18 years old and 41.4% were less than 2 years old. The most common histological diagnosis was iron overload due to major thalassemia (17.5%) followed by biliary atresia (9.7%), no significant pathologic change (8.7%), neonatal hepatitis (8.7%), chronic hepatitis (8.5%), cirrhosis (6.5%), metabolic disease (5.5%) and progressive familial intrahepatic cholestasis (5%). Results of the hemosiderosis grading in patients with thalassemia revealed no or minimal, mild, medium, or marked increase in 10%, 27.1%, 10%, 21.4% and 31.5% of the cases, respectively and the degree of iron deposition rose in parallel with age and also the stage of fibrosis (p< 0.05). Conclusion: A liver biopsy is a useful and practical tool for the appropriate diagnosis of pediatric liver diseases. Also, we found that in non thalassemic children, biliary atresia, chronic hepatitis and neonatal hepatitis, in the stated order, are the most prevalent histologic diagnoses in Iranian pediatrics.